Evaluation of the diet of a selected group of children with coeliac disease - Joanna Rachtan-Janicka (Roczniki Panstwowego Zakladu Higieny)
Introduction Gluten-free diet (GFD) is the only effective treatment for coeliac disease. The aim of GFD is to provide all necessary nutrients, excluding products containing gluten or products contaminated with it.